Oncological Patients With Endocrine Complications After Immunotherapy With Checkpoint Inhibitors Present Longer Progression-Free and Overall Survival - Paschou, Stavroula A.; Liontos, Michael; Eleftherakis-Papaiakovou, Evangelos; Stefanaki, Katerina; Markellos, Christos; Koutsoukos, Konstantinos; Zagouri, Flora; Psaltopoulou, Theodora; Dimopoulos, Meletios-Athanasios (Frontiers in Oncology, 2022)
Aim. To investigate the association of endocrine complications after ICIs immunotherapy with progression free survival (PFS) and overall survival (OS) in a large single-center oncological cohort. Patients and methods. In total, 351 patients were included in the analysis, 248 men (70.7%) and 103 women (29.3%). The median age was 66 years. Patients had a variety of cancer types, namely bladder cancer (131, 37.3%), renal cancer (89, 25.4%), lung cancer (74, 21.1%), ovarian cancer (22, 6.3%) and other types of cancer (35, 10%). The majority (314, 89.4%) were classified as stage IV, while 10.6% (37) were classified as stage III. Most of the patients received immunotherapy with anti-PD1 agents (262, 74.6%) and the rest with anti-PD-L1 agents (89, 25.4%). Kaplan-Meier estimates were used to describe and visualize the effect of categorical variables on OS and PFS. Survival analysis was performed by Kaplan-Meier curves and survival differences between groups were estimated using the log-rank test. The estimation of the prognostic value of several variables with patients’ survival was made by Cox regression models. Results. In total, 68 (19.4%) of patients presented an endocrine complication after immunotherapy with ICIs. Specifically, 66 (18.8%) had thyroid dysfunction, 1 patient presented hypophysitis (0.3%) and 1 patient had combination of thyroid dysfunction and hypophysitis (0.3%). Patients with an endocrine complication had mPFS of 15 months (95% CI 11.0-18.9 months), while in those without endocrine complication mPFS was 7 months (95% CI 6.1-7.9 months, p<0.001). Similarly, median OS (mOS) was statistically significant lower in the patients’ group without endocrine complication. In fact, mOS was 51 months (95% CI 39.3-62.7 months) for these patients. The presence of endocrine complications after immunotherapy with ICIs retained its significance in terms of longer PFS (HR 0.57, 95% CI 0.39-0.81) and OS (HR 0.53, 95% CI 0.32-0.90) after multivariate analysis. Conclusions. ICIs endocrinopathies may be a positive predictor of immunotherapy response.